Guanidinoacetic acid ameliorates hepatic steatosis and inflammation and promotes white adipose tissue browning in middle-aged mice with high-fat-diet-induced obesity - Su, Yuan; Li, Xinrui; Zhao, Jiamin; Ji, Bingzhen; Zhao, Xiaoyi; Feng, Jinxin; Zhao, Junxing (Food & function, 2024)
Guanidinoacetic acid (GAA) is a naturally occurring amino acid derivative that plays a critical role in energy metabolism. In recent years, a growing body of evidence has emerged supporting the importance of GAA in metabolic dysfunction. Hence, we aimed to investigate the effects of GAA on hepatic and adipose tissue metabolism, as well as systemic inflammatory responses in obese middle-aged mice models and attempted to explore the underlying mechanism. We found that dietary supplementation of GAA inhibited inguinal white adipose tissue (iWAT) hypertrophy in high-fat diet (HFD)-fed mice. In addition, GAA supplementation observably decreased the levels of some systemic inflammatory factors, including IL-4, TNF-α, IL-1β, and IL-6. Intriguingly, GAA supplementation ameliorated hepatic steatosis and lipid deposition in HFD-fed mice, which was revealed by decreased levels of TG, TC, LDL-C, PPARγ, SREBP-1c, FASN , ACC , FABP1 , and APOB and increased levels of HDL-C in the liver. Moreover, GAA supplementation increased the expression of browning markers and mitochondrial-related genes in the iWAT. Further investigation showed that dietary GAA promoted the browning of the iWAT via activating the AMPK/Sirt1 signaling pathway and might be associated with futile creatine cycling in obese mice. These results indicate that GAA has the potential to be used as an effective ingredient in dietary interventions and thus may play an important role in ameliorating and preventing HFD-induced obesity and related metabolic diseases. This study provides evidence for the ameliorative effect of dietary guanidinoacetic acid on metabolic disorders in HFD-fed mice.